Evaluation of a Novel Wellness Curriculum on Medical Student Wellbeing and Engagement Demonstrates a Need for Student-Driven Wellness Programming. Issue 1 (13th December 2022) - Edmonds, Victoria S.; Chatterjee, Krishanu; Girardo, Marlene E.; Butterfield, Richard J.; Stonnington, Cynthia M.
Abstract: Problem: Medical training is stressful and has well-established implications for student wellbeing. Despite widespread efforts to reduce student burnout through wellness programming in medical schools, there is a paucity of literature examining students' perception of wellness and engagement with these programs. As such, we sought to evaluate: 1) medical students' level of engagement with a multifaceted wellness curriculum, 2) factors students perceived as important to wellbeing, and 3) associations with longitudinal measures of wellbeing and perceived stress. Intervention: A multipronged wellness curriculum was instituted at Mayo Clinic Alix School of Medicine-AZ (MCASOM-AZ) in 2017. This includes mental health services, curriculum-embedded seminars, wellness committee (composed of students, faculty, and administration) driven programming, and student proposed wellness activities that are reviewed and funded by the committee. The authors invited students at our institution to complete questionnaires at three timepoints during the 2018–2019 academic year. Questionnaires asked participants to rank eight factors from least to most important to their overall wellbeing. Participants self-reported their participation in each prong of the wellness curriculum and ranked the impact of each on their overall wellbeing. Their wellbeing and perceived stress were measured at each timepoint using validated psychological instruments. Context: As MCASOM-AZ opened in 2017, the student body at the time of study consisted of first- and second-year medical students. All students had the opportunity to engage with all aspects of the wellness curriculum and participate in this study, however participation was elective and all responses were anonymous. Of the MCASOM-AZ student body comprised of 100 students, 58 consented to participate in the study, 41.4% of which were Year 1 and 58.6% of which were Year 2 students. Participant age and gender were collected and were representative of the larger student body. Impact: Students engaged most with student-initiated wellness. They perceived unscheduled time as most impactful to their overall wellbeing with student-initiated activities as second-most impactful. Students with higher perceived stress were more likely than others to use mental health resources, which otherwise ranked lower in importance. Ranking academic performance as important to wellbeing was associated with higher wellbeing. There was no difference in wellbeing between students who participated in the wellness curriculum and those who did not. However, overall student wellbeing increased over the course of the year while perceived stress decreased. Lessons Learned: Medical school programs may benefit from allowing students to direct or contribute to the design of their own wellness curriculum. Additionally, medical education should work toward creating a more supportive learning environment with improved flexibility in order to better meet students' individual needs without compromising their education. Despite having low utilization rates overall, mental health resources remain an important aspect of student support services as they are used by students under greater amounts of perceived stress than their peers. Supplemental data for this article is available online at https://doi.org/10.1080/10401334.2021.2004415 .